Behavioral Emotion Regulation Strategies and Symptoms of Psychological Distress Among Turkish University Students - Edib Şevki Keskiner; Ertuğrul Şahin; Nursel Topkaya; Zehra Yiğit (Behavioral Sciences)
The purpose of this study was to examine the association between behavioral emotion regulation strategies and symptoms of depression, anxiety, and stress among Turkish university students. Participants consisted of 633 students continuing their university education in two different universities in Türkiye. Participants completed a data collection tool comprising a Sociodemographic Information Form, the Behavioral Emotion Regulation Questionnaire, and the Depression Anxiety Stress Scales-21. Data were analyzed using descriptive statistics, Pearson’s product-moment correlation coefficient analysis, and multivariate multiple regression analysis. The results of this study revealed that seeking distraction was negatively associated with symptoms of depression, anxiety, and stress, whereas withdrawal, seeking social support, and ignoring were positively associated with symptoms of depression, anxiety, and stress among university students. Additionally, actively approaching was negatively associated with depressive symptoms. Overall, the findings demonstrate that university students who use maladaptive behavioral emotion regulation strategies (e.g., withdrawal, ignoring) tend to have higher levels of psychological distress, whereas university students who use adaptive emotion regulation strategies (e.g., distraction) tend to have lower levels of psychological distress. However, contrary to expectations, seeking social support was positively associated with symptoms of psychological distress. Given the paucity of research on the relationship between behavioral emotion regulation strategies and psychological distress in the Turkish cultural context, this study may contribute to identifying both universal and culturally specific strategies associated with depressive, anxiety, and stress symptoms among Turkish university students.